BAME employees' work experience in the UK public sector: an empirical study of academic and research libraries. Issue 3 (24th February 2022) - Ishaq, Mohammed; Hussain, Asifa Maaria
Abstract : Purpose: The research was aimed at gauging the experiences of Black, Asian and minority ethnic (BAME) staff working in academic and research libraries across the UK, part of the higher education and public sector significantly under researched. Design/methodology/approach: Using an essentially qualitative approach involving a focus group and in-depth interviews, the research design aimed to capture the lived experiences of BAME library employees. Findings: BAME employees are very conscious of their ethnicity due to a feeling of being monitored and under pressure to perform to a higher standard. BAME staff are subjected to verbal racism including microaggression from co-workers. There is no adequate mechanism in place to address the concerns of BAME staff and represent their interests. BAME employees are overrepresented at lower ends of the profession and are not encouraged by line managers to pursue promotion opportunities leading to a distinct lack of diversity at the top level of academic libraries. Research limitations/implications: There are implications for the work experience and career development of BAME library staff, for the leadership and management of libraries and the wider higher education sector to reflect upon. Originality/value: Based on real life experiences of BAME staff, this research plugs a gap in a neglected area of the public and higher education sector and provides an opportunity for managers of academic libraries to reflect on the issues raised and consider interventions.